The Relationship between Food Availability and Nutritional Status of Children Aged 6–24 Months - Ernawati , Dwi; Fazrin, Intan; Maharani, Yovinka; Prasetya, Taufan Agung; Qori Ila Saidah (Journal Of Nursing Practice, 2026)
Background: The growth and development period is the golden phase for toddlers; thus, providing adequate and balanced nutrition is essential to optimize their nutritional status. One of the factors influencing poor nutritional status is limited food availability. Purpose: This study aims to analyse the relationship between food availability and the nutritional status of children aged 6–24 months in the Bulak Banteng Subdistrict, Surabaya. Methods: This study employed a descriptive analytic design with a cross-sectional approach. The population consisted of all children aged 6–24 months in Bulak Banteng Subdistrict, totalling 146 toddlers. A total of 107 respondents were selected using simple random sampling. Food availability, was measured using the Household Food Insecurity Access questionnaire, and nutritional status, was assessed using anthropometric measurements. Data were analysed using the Spearman’s rho test. Results: The findings showed that most households were categorized as food secure, and most children had a good nutritional status. Statistical analysis revealed a significant relationship between food availability and nutritional status (p =0.001, ρ <0 .05). Conclusion: Food availability is significantly associated with the nutritional status of toddlers. Parents demonstrated the ability to maintain good nutritional status in their children; however, they are encouraged to actively participate in nutrition education programs, enhance their knowledge and skills in preparing nutritious meals, and regularly monitor their children’s nutritional status.